2017
DOI: 10.1039/c7ra01392b
|View full text |Cite
|
Sign up to set email alerts
|

Surface patterning of single-walled carbon nanotubes enhances their perturbation on a pulmonary surfactant monolayer: frustrated translocation and bilayer vesiculation

Abstract: In contrast to SWCNTs with unique surface properties, the surface patterning of SWCNTs is found to enhance their perturbation on the pulmonary surfactantsviafrustrated translocation and destructive bilayer vesiculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
(62 reference statements)
1
10
0
1
Order By: Relevance
“…Computational studies can aid in the understanding of the interaction between the surfactant and NPs by providing insights into the molecular level behaviour. Coarse-grained molecular dynamics (CGMD) simulations have been applied to explain the structural and molecular changes in LS due to the inhalation of different types of NPs, for example, carbon nanotubes [10,11,26], fullerene [6,7,27], graphene [28][29][30], silica [31], and others [2,14,[32][33][34]. In addition, the interaction of LS monolayer with other molecules has been investigated, e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational studies can aid in the understanding of the interaction between the surfactant and NPs by providing insights into the molecular level behaviour. Coarse-grained molecular dynamics (CGMD) simulations have been applied to explain the structural and molecular changes in LS due to the inhalation of different types of NPs, for example, carbon nanotubes [10,11,26], fullerene [6,7,27], graphene [28][29][30], silica [31], and others [2,14,[32][33][34]. In addition, the interaction of LS monolayer with other molecules has been investigated, e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Regular inhalation of airborne NPs intensifies the probability of lung ageing, promoting lung malfunction, and can induce serious lung diseases such as asthma, lung cancer, acute respiratory distress syndrome, and more [8,9]. The inhaled NPs interact with the lung surfactant monolayer (LS), the first biological barrier inside the lung alveolus, and may cause serious damage in the surfactant layer [6,10,11]. Furthermore, in experimental studies, it was found that the inhaled NPs may interact with the surfactant components, inhibit normal lung functioning and induce lung diseases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant amount of literature concerning the possible consequences of inhaling airborne nanoparticles (NPs) into the lung. [9][10][11][12][13] Most of these studies, whether computational or experimental, have been concentrated on the effects of common airborne NPs (carbon 14,15 , silica 16 , gold 12,13 , and others [17][18][19] ) on LS monolayer. In these studies, the consequences of airborne NPs inhalation have been investigated in terms of the NPs' size 11 , shape 17 , surface properties (surface charge, hydrophobicity/hydrophilicity) 20 , and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The engineered AuNPs can be a therapeutic and diagnostic agent for cancer by targeting tumour cells [17]. Like other NPs [18][19][20][21], bare AuNPs (engineered or environmental) can alter the surfactant structural and dynamical properties. Experimentally it has been shown that bare AuNPs can disrupt the normal lung function by impeding the ability to lower the surface tension values during alveolus compression [15,16].…”
Section: Introductionmentioning
confidence: 99%